EVALUASI DOSIS DAN PROFIL PENGOBATAN PADA PASIEN DIABETES MELLITUS TIPE 2 KOMPLIKASI NEFROPATI DI RUMAH SAKIT DI KOTA SAMARINDA - Ruslan, Rainhard Duta Pradana; setiawan, Roni; Hanif, Deasy Nur Chairin; Azmi, Rizki Nur (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kota Samarinda, 2023)
The number of Diabetes Milletus cases in the city of Samarinda is 3.04%. One of the complications of uncontrolled DM can cause nephropathy. DM patients with diabetic nephropathy are described as having chronic albuminuria of 300 mg/24 hours on 2 visits 3 to 6 months. The purpose of this study was to look at the profile and treatment evaluation of patients with Diabetes Mellitus Type 2 complications of nephropathy at a hospital in Samarinda City. The method in this study is non-experimental observational with a descriptive design. With a cross-sectional approach using retrospective data, namely looking at data based on medical records of patients with Diabetes Mellitus Type 2 complications of nephropathy at a hospital in Samarinda City. The results of a study conducted at Samarinda City Hospital with a sample of 94 type 2 DM patients with nephropathy complications who were treated at inpatient installations from January 2021 to March 2022. The percentages were obtained based on gender, namely men (45.74%) ) and women (54.26%). The age range of patients with nephropathy DM is between 18-60 years with the most incidence being 41-60 (57.45%). The treatment profile obtained the greatest results using insulin, namely novorapid insulin (43.43%), lantus (19.74%) ), levemir (13.16%). while the oral drug, sulfonylrea (Gliquidone) 30 mg (13.16%). In this study there were 789 (97.65%) correct doses of 808 drugs and 19 (2.35%) incorrect doses. drug cases that require adjustment of drug dosage because it is influenced by the GFR value. Keywords: Type 2 Diabetes Mellitus, Dosage Evaluation, Nephropathy Complications, Treatment Profile.